WHAT FACTORS INFLUENCE AD ATTENTION AND AD AVOIDANCE ON SOCIAL MEDIA? STUDY: ON THE MILLENNIAL AND GENERATION Z - Broto, Ibnu Kuncoro (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Currently, online media has become a favorite for brands to introduce their products to the public. However, social media users pay little attention to advertisements and social media users block advertisements or avoid advertisements to maintain their privacy. This research aims to examine the factors that influence attention to advertising and avoidance of advertising. The sample in this research is the millennial generation and Generation Z as social media users on Instagram and Facebook. The number of samples in this study was 268 respondents, and the data analysis technique used SEM-PLS. The findings of the research are that ad relevance has a positive effect on attention to social emedia ads, and privacy concerns increase ad avoidance. This study also found that Ad engagement had a positive effect on ad attention and a negative effect on ad avoidance. Ad engagement also mediates the relationship between ad relevance, ad attention, and ad avoidance. It suggests that personalized advertising will further increase consumers' attention to the ad and reduce ad avoidance behavior if consumers are cognitively engaged with the ad.